Surface Analyses of PVDF/NMP/[EMIM][TFSI] Solid Polymer Electrolyte - Sedlak, Petr; Sobola, Dinara; Gajdos, Adam; Dallaev, Rashid; Nebojsa, Alois; Kubersky, Petr (Polymers, 2021)
Thermal treatment conditions of solid polymer polymer electrolyte (SPE) were studied with respect to their impact on the surface morphology, phase composition and chemical composition of an imidazolium ionic-liquid-based SPE, namely PVDF/NMP/[EMIM][TFSI] electrolyte. These investigations were done using scanning electron microscopy, Raman spectroscopy, Fourier transform infrared spectroscopy, differential scanning calorimetry as well as X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectroscopy. A thoroughly mixed blend of polymer matrix, ionic liquid and solvent was deposited on a ceramic substrate and was kept at a certain temperature for a specific time in order to achieve varying crystallinity. The morphology of all the electrolytes consists of spherulites whose average diameter increases with solvent evaporation rate. Raman mapping shows that these spherulites have a semicrystalline structure and the area between them is an amorphous region. Analysis of FTIR spectra as well as Raman spectroscopy showed that the β-phase becomes dominant over other phases, while DSC technique indicated decrease of crystallinity as the solvent evaporation rate increases. XPS and ToF-SIMS indicated that the chemical composition of the surface of the SPE samples with the highest solvent evaporation rate approaches the composition of the ionic liquid.
Keywords: X-ray photoelectron spectroscopy; solvent evaporation; solid polymer electrolyte; crystallinity; poly-(vinylidene fluoride); secondary ion mass spectroscopy; Fourier transform infrared spectroscopy; imidazolium ionic liquids; Raman spectroscopy